2016
DOI: 10.1016/j.chb.2016.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Avatar-mediated creativity: When embodying inventors makes engineers more creative

Abstract: is an open access repository that collects the work of Arts et Métiers ParisTech researchers and makes it freely available over the web where possible. This is an author-deposited version published in: https://sam.ensam.eu Handle ID: .http://hdl.handle.net/10985/12194 To cite this version :Jérôme GUEGAN, Stéphanie BUISINE, Fabrice MANTELET, Nicolas MARANZANA, Frédéric SEGONDS -Avatar-mediated creativity: When embodying inventors makes engineers more creative -Avatar-mediated creativity: When embodying inventor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
76
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 117 publications
(93 citation statements)
references
References 46 publications
(51 reference statements)
1
76
0
2
Order By: Relevance
“…This means that the appearance of an avatar not only influences users' behavior in the virtual world, but also in the real world. Finally, a recent study (Guegan, Buisine, Mantelet, Maranzana, & Segonds, 2016) showed that avatars looking like inventors increase the creative performance of engineers. This benefit also endured over time and participants allocated to inventor avatars continued to perform better in a subsequent face-to-face creativity task.…”
Section: Introductionmentioning
confidence: 98%
“…This means that the appearance of an avatar not only influences users' behavior in the virtual world, but also in the real world. Finally, a recent study (Guegan, Buisine, Mantelet, Maranzana, & Segonds, 2016) showed that avatars looking like inventors increase the creative performance of engineers. This benefit also endured over time and participants allocated to inventor avatars continued to perform better in a subsequent face-to-face creativity task.…”
Section: Introductionmentioning
confidence: 98%
“…However, previous work shows that the digital self-representations can influence behavior in a pro or antisocial way. For example, the embodiment of an avatar resembling an inventor led engineering students to show higher creative fluency and originality of ideas during a face-to-face brainstorming session conducted after immersion in a virtual environment (Guegan et al, 2016). Another example shows that embodying a casually dressed black avatar enhances users' performance in playing drums in comparison to embodying a formally dressed white avatar (Kilteni et al, 2013), probably due to the positive stereotypic association of black individuals and rhythm.…”
Section: Manipulation Of Interoceptive Signals: Affecting Emotion Regmentioning
confidence: 99%
“…In a second study, they also observed that tall avatars lead to more confident behavior than short avatars in a negotiation task. More recent studies have also shown that the appearance of the embodied avatars could influence attitudes, beliefs (Fox et al, 2013) and actions of the users (Peña et al, 2009;Guegan et al, 2016). For instance, it has been shown in nonimmersive VR environments that the use of an avatar resembling a member of the Ku Klux Klan activates more negative thoughts and leads users to participate more aggressively (e.g., murder, vengeance) in the stories created (Peña et al, 2009).…”
Section: Manipulation Of Interoceptive Signals: Affecting Emotion Regmentioning
confidence: 99%
“…antisocial behavior (Peña, Hancock, & Merola, 2009;Yoon & Vargas, 2014), food choice (Fox, Bailenson, & Binney, 2009;Sah, Ratan, Sandy Tsai, Peng, & Sarinopoulos, 2016), physical exercise (Li, Lwin, & Jung, 2014;Peña, Khan, & Alexopoulos, 2016;Peña & Kim, 2014), racial bias (Aviles, 2017;Peck, Seinfeld, Aglioti, & Slater, 2013), body dissatisfaction (Fox, Bailenson, & Tricase, 2013;Sylvia, King, & Morse, 2014), financial risk-taking (Hershfield et al, 2011), consumer choices (Ahn & Bailenson, 2011), math performance (Lee, Nass, & Bailenson, 2014;Ratan & Sah, 2015), student engagement , and creative thinking (Buisine, Guegan, Barré, Segonds, & Aoussat, 2016;de Rooij, van der Land, & van Erp, 2017;Guegan, Buisine, Mantelet, Maranzana, & Segonds, 2016).…”
mentioning
confidence: 99%
“…Although the Proteus effect may seem like a valid phenomenon given the broad array of contexts within which it has been tested and supported, these tests have not provided consistent evidence for the effect, with some studies unable to replicate the effect at all (Kaye, Pennington, & McCann, 2018;Sylvia et al, 2014) while others find medium-to-large effects sizes (Banakou, Groten, & Slater, 2013;Guegan et al, 2016). Hence, the present research aims to provide clarity about the reliability and size of the Proteus effect by offering the first meta-analysis of previous research on the phenomenon.…”
mentioning
confidence: 99%